2018
DOI: 10.5688/ajpe6110
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Peer-led Education in Patient Safety Training

Abstract: Objective. To examine the literature pertaining to the use of peer-led education in patient safety. Findings. Four studies met the inclusion criteria: two were conducted in health care students and two in medical practitioners. Three studies used pre-post evaluation, with one containing a comparator group. One study a post-intervention evaluation only. All studies undertook Kirkpatrick Level 2 evaluations, showing significant improvements in attitudes and knowledge. One study undertook Level 3 and 4 evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…According to Walpola et al. (2018), education has been widely regarded as a basic method to enhance patient safety in healthcare settings. Furthermore, Stefan, the president of the World Federation for Medical Education, ever said: “patient safety is a necessary competency and thus required to be introduced early and then strengthened throughout school education and continuing professional advancement” (Wu & Busch, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to Walpola et al. (2018), education has been widely regarded as a basic method to enhance patient safety in healthcare settings. Furthermore, Stefan, the president of the World Federation for Medical Education, ever said: “patient safety is a necessary competency and thus required to be introduced early and then strengthened throughout school education and continuing professional advancement” (Wu & Busch, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Literature describes peer-led education as a powerful approach to achieving program goals and objectives [26][27][28]. To our knowledge, using a peer-led approach to implementation has not been directly studied, however our case shows the potential for such an approach.…”
Section: Peer-to-peer Implementationmentioning
confidence: 85%
“…In Ontario, a team-based COPD management program (BCC) based in primary care focusing on patient selfmanagement through education, skills training and case management, was spread from the region where it was originally developed and implemented, to a neighbouring region using a peer-to-peer implementation approach. While current literature lacks a clear definition, or common name for peer-to-peer approaches in implementation, in general terms, peer-to-peer approaches involve using peer-led education and peer assessment as a method to support learning about the intervention [26][27][28]. Using a peer-to-peer approach implementation processes can facilitate buy-in and successful uptake/ program implementation [27].…”
Section: Introductionmentioning
confidence: 99%
“… Ip et al's (2013) longitudinal study reported that mandatory peer-to-peer consultation in radiology medical management reduced costs by limiting inappropriate use of high-cost imaging studies. A separate scoping review of four studies evaluated the efficacy of peer-led education in improving patient safety ( Walpola, McLachlan, & Chen, 2018 ). Teams in PC utilizing training of peer-to-PCPs (i.e., MDs, nurse practitioners [NPs]) and peer-to-registered nurses (RNs) were able to promote improving deprescribing practices.…”
Section: Peer-led Education As An Intervention To Support Translationmentioning
confidence: 99%